(untitled) (The Conference Hub, 2025)
During pregnancy, dietary patterns have a direct impact on maternal adaptive processes and fetal development. Disruption of eating patterns, deficiencies of micro- and macronutrients, irregular meal timing, and diets characterized by a high glycemic load are increasingly recognized as significant risk factors contributing to the development of severe forms of pregnancy toxicosis.